The Preparation of Stewards with the Mastery Rubric for Stewardship: Re-Envisioning the Formation of Scholars and Practitioners - Christopher M. Rios; Chris M. Golde; Rochelle E. Tractenberg (MDPI AG, 2019)
A steward of the discipline was originally defined as "someone who will creatively generate new knowledge, critically conserve valuable and useful ideas, and responsibly transform those understandings through writing, teaching, and application". This construct was articulated to support and strengthen doctoral education. The purpose of this paper is to expand the construct of stewardship so that it can be applied to both scholars and non-academic practitioners, and can be initiated earlier than doctoral education. To accomplish and justify this, we describe a general developmental trajectory supporting cross-curriculum teaching for stewardship of a discipline as well as of a profession. We argue that the most important features of stewardship, comprising the public trust for the future of their discipline or profession, are obtainable by all practitioners, and are not limited to those who have completed doctoral training. The developmental trajectory is defined using the Mastery Rubric construct, which requires articulating the knowledge, skills, and abilities (KSAs) to be targeted with a curriculum; recognizable stages of performance of these KSAs; and performance level descriptors of each KSA at each stage. Concrete KSAs of stewardship that can be taught and practiced throughout the career (professional or scholarly) were derived directly from the original definition. We used the European guild structure's stages of Novice, Apprentice, Journeyman, and Master for the trajectory, and through a consensus-based standard setting exercise, created performance level descriptors featuring development of Bloom's taxonometric cognitive abilities (see Appendix A) for each KSA. Together, these create the Mastery Rubric for Stewardship (MR-S). The MR-S articulates how stewardly behavior can be cultivated and documented for individuals in any disciplinary curriculum, whether research-intensive (preparing "scholars") or professional (preparing members of a profession or more generally for the work force). We qualitatively assess the validity of the MR-S by examining its applicability to, and concordance with professional practice standards in three diverse disciplinary examples: (1) History; (2) Statistics and Data Science; and (3) Neurosciences. These domains differ dramatically in terms of content and methodologies, but students in each discipline could either continue on to doctoral training and scholarship, or utilize doctoral or pre-doctoral training in other professions. The MR-S is highly aligned with the practice standards of all three of these domains, suggesting that stewardship can be meaningfully cultivated and utilized by those working in or outside of academia, supporting the initiation of stewardship prior to doctoral training and for all students, not only those who will earn PhDs or be scholars first and foremost. The MR-S can be used for curriculum development or revision in order to purposefully promote stewardship at all levels of higher education and beyond. The MR-S renders features of professional stewardship accessible to all practitioners, enabling formal and informal, as well as self-directed, development and refinement of a professional identity.